PREDICTORS OF RE-BLEEDING AFTER OESOPHAGEAL VARICEAL BANDING IN CIRRHOTIC PATIENTS AT 4 WEEKS - Shoaib Asghar; Junaid Mustafa; Habib ur Rehman; Muhammad Kamran Farooq; Muhammad Umar Waheed; Salman Shahid (Journal of Ayub Medical College Abbottabad, 2023)
Background: Acute upper gastrointestinal bleeding is a serious complication in cirrhotic patients. Without recommended management, recurrent bleeding happens in 30-40% within the next 2-3 days, and up to 60% within 1 week. Aim was to determine predictors of re-bleeding after oesophageal variceal banding in cirrhotic patients for 4 weeks. It was a descriptive study, conducted at the Department of Medicine, Sheikh Zayed Hospital, Rahim Yar Khan. Six months from June 21 to December 21, 2021. Methods: A total of 93 patients with active oesophageal variceal bleeding were included in this study. Upper gastrointestinal (UGI) endoscopy was performed to look for bendable varices (grades 1-4) and band ligation was applied. Patients were followed for 4 weeks for the history of hematemesis or Malena, fall in haemoglobin of 2 grams per decilitre or more and endoscopic rebleeding findings. Results: Out of 93 patients, 67(72.0%) were males, while 26(28.0%) were females. The Mean age of the patients was 45.66±16.61 years. According to Child-Pugh Classification, the majority of the patients 45(48.4%) had Child-Pugh Class-A, while 33 (35.5%) were Child B and 15 (16.1%) patients belonged to Child-Pugh Class C. Red wale sign was noted in 22 patients (23.7%). Among 93 cirrhotic patients who presented with variceal bleeding, 9 (9.7%) had re-bleeding within 4 weeks. Amongst 9 patients, 8 patients (88.9%) had red wale sign, grade II or above oesophageal varices and belonged to severe liver disease with child class B or C. Conclusion: Endoscopic variceal band Ligation is an effective treatment modality for the control of oesophageal variceal bleeding. Re-bleeding after band ligation was 9.7%. The major contributing factors to re-bleeding were the severity of cirrhosis, grades and columns of oesophageal varices, number of bands ligation and findings of red wale sign. Increasing age and duration of cirrhosis were contributing predictors of increased re-bleeding risk